Efisiensi Persediaan dan Distribusi Melalui Integrasi Supply Chain Management - Ridwan, Mohamad; Gaffar, Mohammad Rizal (Applied Business and Administration Journal, 2022)
Digital transformation requires companies to be able to meet consumer demands responsively. Customer satisfaction can be achieved if the company can provide appropriate products when there is demand. From this, it can be seen that inventory and distribution play an important role in the company, especially manufacturing companies. Therefore, the company must be able to ensure that the inventory and distribution carried out by the company is optimal, or in other words, the company must be able to ensure that there is no shortage or excess inventory and ensure that the product reaches the consumer at the right location, cost, and time. To get stock and distribution run optimally, companies need to manage product flow from upstream, namely the producers of raw materials to downstream, namely end users. Product management can be maximized by integrating supply chain management. By integrating supply chain management, companies will be able to view, calculate and monitor inventory in the warehouse. The benefits that will be obtained by the company through the integration of supply chain management include the company being able to optimize the amount of inventory, delivery, cut costs, and improve services so that customer satisfaction can be met. Through this article, the researcher seeks to see how the integration of supply chain management can improve the efficiency of inventory and product distribution of a company. In this article, the researcher will use a literature study approach to review the efficiency of supply chain management integration in a company.